Examining Gen Z's intention using halal toiletries: Theory of planned behavior and perceived risk - Andani, Listia; Bundo, Mayang; Ramly, Arroyyan (Center for Islamic Economics and Development Studies [P3EI], 2024)
Purpose – This study aimed to formulate a conceptual framework to investigate the influence of attitude, perceived behavioral control, subjective norms, financial risk, social risk, and security risk on the intention to use halal toiletries among Gen Z consumers in West Java.Methodology – Purposive sampling was used in this study. The respondents were 400 Gen Z Muslims residing in West Java Province. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS).Findings – Variables from the Theory of Planned Behavior (attitude, subjective norms, and perceived behavioral control) positively influenced the intention to use halal toiletries. Financial, social, and security risks negatively impact Gen Z consumers' intentions to use halal toiletries.Implications – Halal toiletries should focus on enhancing product performance to receive positive consumer feedback and increase interest. Additionally, they need to promote community engagement; improve product accessibility and user-friendliness; and address security, social, and financial risks to effectively boost consumer intention.Originality – This research integrates components of risk perception with the Theory to create a comprehensive framework for understanding Gen Z’s intention to use halal toiletries. It contributes to the literature by highlighting how specific types of risks impact consumer intentions and offers actionable recommendations for the halal toiletries industry based on empirical evidence.